2001
DOI: 10.1161/01.str.32.6.1291
|View full text |Cite
|
Sign up to set email alerts
|

Power Transcranial Doppler Ultrasound in the Detection of Intracranial Aneurysms

Abstract: Background and Purpose-We sought to perform a large, prospective, multicenter, blinded study comparing power transcranial color duplex sonography (power TCDS) with intra-arterial digital subtraction angiography (IADSA) in the detection of intracranial aneurysms. Methods-Contemporaneous TCDS and IADSA examinations were performed in 171 subjects with suspected intracranial aneurysm. Via the temporal bone window, a 2-dimensional hand-held noncontrast transcranial duplex ultrasound imaging system was used operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
0
11
0
2
Order By: Relevance
“…Studies using transcranial color-coded duplex sonography (TCCS) compared to TCD have reported better rates of transtemporal window presence (81-92%) [24][25][26][27][28][29] . However, Krejza et al [16] did not notice any clear difference in the prevalence of transtemporal windows between TCCS and TCD.…”
Section: Prevalence Of Acoustic Windowsmentioning
confidence: 99%
“…Studies using transcranial color-coded duplex sonography (TCCS) compared to TCD have reported better rates of transtemporal window presence (81-92%) [24][25][26][27][28][29] . However, Krejza et al [16] did not notice any clear difference in the prevalence of transtemporal windows between TCCS and TCD.…”
Section: Prevalence Of Acoustic Windowsmentioning
confidence: 99%
“…This places high demands on the frame rate and processing capacity of the duplex scanner. TCDI should not be used as a screening test for cerebral aneurysms [23,24]. Furthermore, fewer diagnostic criteria are available for the detection and grading of intracranial disease with TCDI [25,26] Although TCDI allows the assessment of intracranial veins, thrombosis and arterio-venous malformations [27][28][29], the reliability and clinical utility of TCDI in this setting are still unknown.…”
Section: Limitations Of Tcdimentioning
confidence: 99%
“…22,23 Contrast enhancement, in conjunction with power Doppler, allows the imaging of low-flow signals and decreases the dependence of the angle of insonation. 12 This can assist in the detection of low-velocity flow around and within the coil nidus. Indeed, we found the greatest increase in detection with contrast was in aneurysms with minor refilling.…”
Section: Turner Et Al Ultrasound-assessed Coiled Intracranial Aneurysmentioning
confidence: 99%
“…A criticism of TCCS imaging of the intracranial vasculature is the degree of operator expertise required. Although it is accepted that TCCS requires experience, particularly when using contrast agents, White et al 12 conducted a study comparing the performance of experienced and inexperienced operators. They found very little difference in the detection of aneurysms between the 2 groups (sensitivity 5%, specificity 2%).…”
Section: Turner Et Al Ultrasound-assessed Coiled Intracranial Aneurysmentioning
confidence: 99%